Prevalence and Spectrum of Predisposition Genes With Germline Mutations Among Chinese Patients With Bowel Cancer - Xie, Zhengyong; Ke, Yongli; Chen, Junyong; Li, Zehang; Wang, Changzheng; Chen, Yuhong; Ding, Hongliang; Cheng, Liyang (Frontiers in Genetics, 2022)
Background: Bowel cancer is the third-most common cancer and the second leading cause of cancer death worldwide. Bowel cancer has a substantial hereditary component; however, other than their association with Lynch syndrome, the other hereditary risk factors to bowel cancer pathogenesis have not been systematically defined. Materials and Methods: A total of 573 bowel cancer patients were enrolled in this study, of which 93.72% were colorectal cancer, and we integrated germline mutation with somatic mutation information utilizing target next-generation sequencing. Results: Pathogenic/Likely Pathogenic (P/LP) germline alterations were identified in 47 (8.2%) bowel cancer patients and the ratio of bowel cancer patients with family history was significantly higher in the P/LP group than the non-pathogenic (Non-P) group. Some rare germline alterations, such as FANCD2, CDH1, FLCN, were found and 32 patients (68.1%) had germline alterations in DNA-damage repair (DDR) genes, of which homologous recombination (HR) accounted for the highest proportion. Comparing 573 case-patients with bowel cancer with reference controls (ChinaMAP database), significant associations were observed between bowel cancer and mutations in APC, ATM, MLH1, FANCD2, MSH3, MSH6, PMS1, and RAD51D. Somatic gene differential analysis revealed a remarkable difference in eighteen genes and a significant difference was also found in tumor mutation burden (TMB) between germline mutation carriers and non-germline mutation individuals. Besides, TMB in DDR mutation groups showed a dramatic difference compared with the non-DDR mutation group. However, there is no statistical difference of TMB among detailed DDR pathways for bowel cancer patients no matter with or without germline mutation. Moreover, a significantly higher level of mutation count in the DDR group was observed from The Cancer Genome Atlas (TCGA) database and DDR and non-DDR alteration groups displayed various immune profiles. Conclusion: Chinese bowel cancer patients in our cohort have a distinct spectrum of germline variants, with remarkable molecular characteristics like TMB and DDR. Furthermore, somatic mutations obtained from The Cancer Genome Atlas (TCGA) database indicated that a deeper understanding of interactions among DDR and immune cells would be useful to further investigate the role of DDR in bowel cancer.